Validity and reliability of the Arabic translation of the child oral-health-related quality of life questionnaire (CPQ 11ÃƒÂ¢Ã‹â€ Ã¢â‚¬â„¢14) in Saudi Arabia - A. BROWN, & Z. AL-KHAYAL (Paediatric Dentistry, 2006)
Oral health has been defined as the standard of health of oral and related tissues that enables individuals to eat, speak and socialize without active disease, discomfort or embarrassment, and that contributes to general well-being [1].